Case for diagnosis. Systemic light chain amyloidosis with cutaneous involvement - João Renato Vianna Gontijo; Jackson Machado Pinto; Maysa Carla de Paula (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Systemic light chain amiloydosis is a rare disease. Due to its typical cutaneous lesions, dermatologists play an essential role in its diagnosis. Clinical manifestations vary according to the affected organ and are often unspecific. Definitive diagnosis is achieved through biopsy. We report a patient with palpebral amyloidosis, typical bilateral ecchymoses and cardiac involvement, without plasma cell dyscrasia or lymphomas. The patient died shortly after the diagnosis.